Hepcidin and DNA promoter methylation in hepatocellular carcinoma. (28th December 2017) - Udali, Silvia; Castagna, Annalisa; Corbella, Michela; Ruzzenente, Andrea; Moruzzi, Sara; Mazzi, Filippo; Campagnaro, Tommaso; De Santis, Domenica; Franceschi, Antonia; Pattini, Patrizia; Gottardo, Rossella; Olivieri, Oliviero; et al.
Abstract: Background: The liver hormone hepcidin regulates iron homoeostasis that is often altered in hepatocellular carcinoma (HCC). Epigenetic phenomena control gene expression through a dynamic fashion; therefore, considering the plasticity of both iron homoeostasis and epigenetic mechanisms and their role in liver carcinogenesis, we investigated whether hepcidin gene ( HAMP ) expression is modulated by DNA methylation, thus affecting iron status in human HCC. Materials and methods: Thirty‐two patients affected by nonviral HCC were enrolled, and their main clinical and biochemical characteristics were obtained. Neoplastic and homologous non‐neoplastic liver tissues were analysed for HAMP promoter DNA methylation, for HAMP gene expression and for iron content. An in vitro demethylation assay with a human hepatocarcinoma cell line was performed to evaluate the role of DNA methylation on HAMP transcriptional repression. Results: Gene expression and DNA methylation analyses on tissues showed that HAMP was transcriptionally repressed in HCC tissues consensually with a promoter hypermethylation. Furthermore, patients with HCC had low serum hepcidin concentrations, and HCC tissues had relative iron depletion as compared to non‐neoplastic liver tissues. The cell culture model showed the functional role of DNA hypermethylation by downregulating HAMP gene expression. Through a quantitative methylation analysis on HCC tissues, we then proved that methylation at definite CpG sites within consensus sequences for specific transcription factors is possibly the mechanism underlying HAMP repression. Conclusions: This study highlights a novel role for HAMP downregulation through DNA promoter hypermethylation and emphasises the significance of epigenetics in the regulation of iron metabolism in HCC.